The Impact of Digital Transformation in Higher Education Management: Integrating Online Learning and Educational Applications for Efficiency and Accessibility - Dhameria, Vita; Muazeib, Ahmed Ibrahim Maymoun; Blhaj, Khaled Mohamed Salem; Sugiyarsih, Susi; Rosadah, Ros Awaliyah (Qualitative and Quantitative Research Center, 2025)
In the era of the Fifth Industrial Revolution, digital transformation has become a strategic necessity in higher education management, particularly in achieving institutional efficiency and accessibility. Universities today are required to integrate digital technologies comprehensively through online learning and educational applications to address the growing complexity of academic management and to expand the reach of educational services. This study aims to examine the impact of digital transformation on managerial efficiency and accessibility in higher education, with the mediating roles of online learning integration and the use of educational applications. A quantitative approach was employed through a survey involving 250 academic community members from Indonesia and Libya. Data were analyzed using Structural Equation Modeling with AMOS software. The results revealed that digital transformation significantly influenced both online learning integration and the utilization of educational applications. These two mediating variables contributed positively to enhancing institutional efficiency and directly supported broader access to higher education. The findings underscored that successful digitalization in higher education management depended not only on technological adoption but also on integrative strategies that linked digital platforms and application systems. This study contributes practical insights for universities to strategically optimize online learning and educational applications as core drivers of efficient and inclusive digital transformation in higher education.